Does workplace envy always have detrimental consequences in organizations? A study of public and private sector employees - (:unkn) unknown (EMERALD GROUP PUBLISHING LTD, 2022)
Purpose Based on the situational approach for envy, the purpose of this paper is to examine the effect of two-dimensional workplace envy (being envied and envying others) on the task and contextual performance of employees working in either private or public sector organizations. Design/methodology/approach This study was conducted on survey data collected from 988 private sector employees and 530 employees from the public sector employed in Istanbul. Following a quantitative empirical design, structural equation modeling was used to test the hypotheses. Findings The study results revealed that envying-others dimension has a significant negative effect on both task performance and contextual performance. In addition, the findings indicate more envious feelings of private sector employees than public sector employees. For public sector employees, male participants were found to envy others more than females. Research limitations/implications In addition to the contributions, this study has its limitations. First, although the study was carried out with a comprehensive sample, it is limited to the views of 1,518 employees in Istanbul and is a cross-sectional study. Also, employee performance is evaluated through self-reporting, which forms another limitation; it could have been more reliable for the supervisors to assess their subordinates' performance. Practical implications Apart from scholars, our findings have implications for practitioners. Feelings such as envy that comes with a sense of competition can create an environment that stimulates people, motivates them to work, can make them productive and can also cause an ultimately destructive situation. This makes it critical to manage envy in the workplace. Though there may be facilitators behind it, one crucial factor that fuels envy in the workplace is the lack of fair human resources policies and systems. Still, human resources management is undeveloped in most public organizations. With effective human resources management, there may be some roadmaps for managers to dissolve conflicts arising from envy. First, it is imperative to have systems that will separate the employee from the others, which everyone will accept, strengthening the feelings of justice among employees. Envy often occurs following a social comparison. Management can implement an incentive system that supports employee collaboration and avoid nepotism. Especially in private organizations where the competition is more among employees, managers should give more attention to understand their subordinates' feelings. The managers' attention to expressing their feelings toward their subordinates could establish an equal distance within the workplace. In this sense, language selection is critical, and managers should be mindful of linguistic triggers. Managers should not avoid giving both positive and negative feedback to their employees. Unwarranted and unsystematic reward and/or punishment systems, made with the good intentions of increasing competition, can trigger envy. Finally, managers should implement an open-door policy and open communication that will encourage all team members to be transparent to each other. Originality/value The study was based on a rationale that envy has detrimental workplace outcomes that lead to low task and contextual performance. Although there exists a recent interest for examining the relation between workplace envy and employee performance, based on being envied and envying others dimensions, these studies are limited. This study focuses on these dimensions and performance relations, and it also provides a comparative outlook for public and private sector employees in Turkey in terms of workplace envy.
Keywords: Workplace envy; Task performance; Contextual performance; COUNTERPRODUCTIVE WORK BEHAVIORS; JOB-PERFORMANCE; DISPOSITIONAL ENVY; ROMANTIC JEALOUSY; TASK-PERFORMANCE; MODEL; CITIZENSHIP; ANTECEDENTS; EXPERIENCES; PREDICTORS